2022
DOI: 10.1186/s12906-022-03763-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of Zishen Yutai pills in treating premature ovarian failure determined by integrating UHPLC-Q-TOF-MS and network pharmacology analysis

Abstract: Background Zishen Yutai (ZSYT) pill, a patent Chinese medicine, has been widely used in the treatment of infertility, abortion, and adjunctive treatment of in vitro fertilization (IVF) for decades. Recently, the results of clinical observations showed that premature ovarian failure (POF) patients exhibited improved expression of steroids and clinical symptoms associated with hormone disorders after treatment with Zishen Yutai pills. However, the pharmacological mechanism of action of these pill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Meanwhile, a metabonomic study also suggested that metabolites involved in various pathways and biological processes that may related to the improvement of endometrium receptivity and oocyte quality after ZYP administration (20). A virtual screening further indicated that regulation of neuroactive ligand-receptor interaction, steroid hormone biosynthesis, and ovarian steroidogenesis might be the potential therapeutic mechanism of ZYP in treating premature ovarian failure (POF) (21). Clinically, ZYP used in the luteal phase was reported to improve pregnancy outcomes among patients undergoing IVF-ET (22).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a metabonomic study also suggested that metabolites involved in various pathways and biological processes that may related to the improvement of endometrium receptivity and oocyte quality after ZYP administration (20). A virtual screening further indicated that regulation of neuroactive ligand-receptor interaction, steroid hormone biosynthesis, and ovarian steroidogenesis might be the potential therapeutic mechanism of ZYP in treating premature ovarian failure (POF) (21). Clinically, ZYP used in the luteal phase was reported to improve pregnancy outcomes among patients undergoing IVF-ET (22).…”
Section: Introductionmentioning
confidence: 99%